PENGARUH EDUKASI KESEHATAN TERHADAP PENINGKATAN PENGETAHUAN TENTANG PENTINGNYA SARAPAN PADA SISWA SEKOLAH DASAR DI KECAMATAN MEDAN SUNGGAL KOTA MEDAN - sembiring, bungamari; Hamzah, Diza Fathamira; Handayani, Fitri; Sirajuddin, Inayyah Nur Fitry (Jurnal Penelitian Kesmasy, 2025)
Breakfast is an important habit to support learning concentration, energy fulfillment, and prevent nutritional disorders in elementary school children. However, most children still skip breakfast due to a lack of knowledge and awareness about the importance of a healthy breakfast. This study aims to determine the effect of health education on increasing knowledge about the importance of breakfast among elementary school students in Medan Sunggal District, Medan City. This study used a pre-experimental one group pretest–posttest design. Data collection was conducted through interviews using a structured questionnaire that measured the level of student knowledge before and after being given health education. Education was carried out through an interactive lecture method with video media about balanced nutrition. Data were analyzed using a paired t-test at a 95% confidence level. The results showed a significant increase in knowledge scores after health education (p < 0.000). This indicates that health education has an effect on increasing student knowledge about the importance of breakfast. It is hoped that schools and parents will collaborate continuously through educational activities about nutrition and health as an effort to prevent nutritional problems in elementary school students who are the next generation of the nation